Mesophotic Coral Ecosystems of the Great Barrier Reef Are Understudied and Underexplored - Eyal, Gal; Laverick, Jack H.; Bongaerts, Pim; Levy, Oren; Pandolfi, John M. (Frontiers in Marine Science, 2021)
Mesophotic coral ecosystems (MCEs) are characterised by the presence of photosynthetically active organisms such as corals and algae, and associated communities at depths ranging from 30 to 150 m in tropical and subtropical regions. Due to the increased awareness of the potential importance of these reefs as an integral part of coral reef ecosystems (i.e. deep reef refuge; specialised biodiversity; transition zone between shallow and deep-sea environments; recreational and intrinsic values), interest from the scientific community has grown around the world over the last two decades. Several nations have already made management declarations and started to extend marine protected areas and fishery management to MCEs. The estimated area of Australian MCEs is likely equivalent to that of shallow reef ecosystems down to 30 m; however, Australian MCEs attract limited research effort compared to other major coral reef regions around the world. In this perspective, we briefly explore the reasons for this scarcity of research on mesophotic ecosystems of the Great Barrier Reef (GBR) of Australia (e.g. strict diving regulations; new researchers' involvement; logistics and cost). At present, research efforts on the mesophotic ecosystems of the GBR are in decline and if this trajectory is maintained, the global disparity in knowledge between MCEs near Australia and those from the other main coral reef regions worldwide will sharpen deeply. We call for action from the research community, grant agencies, and decision-makers toward a wider understanding of these important ecosystems in Australia.